Pengaruh Promosi Tanggal Kembar dalam Upaya Meningkatkan Keputusan Pembelian pada Shopee JPSCOdivision Bandung - Khinanty Noviyanty; Tiris Sudrartono (Ekonomis: Journal of Economics and Business, 2026)
This study aims to determine the effect of the Twin Date Promotion in increasing purchasing decisions at Shopee JPSCOdivision Bandung using a quantitative approach. Data collection techniques were carried out through an online questionnaire using Google to 99 consumers at JPSCOdivision selected using a purposive sampling technique. The analytical tool used in this study was simple linear regression. The results of this study revealed that the Twin Date Promotion had a positive and significant effect on purchasing decisions at Shopee JPSCOdivision Bandung.